2013
DOI: 10.1152/ajpendo.00268.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of stearoyl-CoA desaturase-1 in skeletal muscle function and metabolism

Abstract: Stamatikos AD, Paton CM. Role of stearoyl-CoA desaturase-1 in skeletal muscle function and metabolism. Am J Physiol Endocrinol Metab 305: E767-E775,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 91 publications
2
18
0
1
Order By: Relevance
“…SCD1 desaturase indices are good biomarkers for actual enzyme activity and have also been proposed as a good clinical indicator of SCD1 gene expression. Hence, to assess SCD1 activity we calculated two different SCD1 indices by dividing the total concentration of 16:1 with 16:0 (SCD-16) and 18:1 with 18:0 (SCD-18) in each lipid fraction from serum and liver extracts [25, 27]. In the HFD group, the SCD-16 and SCD-18 indices were decreased in the liver TAG, DAG, and PL fractions as well as fasting systemic serum TAG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SCD1 desaturase indices are good biomarkers for actual enzyme activity and have also been proposed as a good clinical indicator of SCD1 gene expression. Hence, to assess SCD1 activity we calculated two different SCD1 indices by dividing the total concentration of 16:1 with 16:0 (SCD-16) and 18:1 with 18:0 (SCD-18) in each lipid fraction from serum and liver extracts [25, 27]. In the HFD group, the SCD-16 and SCD-18 indices were decreased in the liver TAG, DAG, and PL fractions as well as fasting systemic serum TAG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…De novo fatty acid synthesis (also referred to as de novo lipogenesis) occurs from the generation of C16:0 by the FASN in cytoplasm [42]. After the formation of palmitate, a series of chain elongations and desaturations occurs involving SCD and ELOVLs, to generate unsaturated or long-chain fatty acids [43,44]. A previous study reported that SCD can have a strong effect on fatty acid composition within skeletal muscle by converting SFA into MUFA [20].…”
Section: Expression Regulation Of Genes Involved In Lipogenesismentioning
confidence: 99%
“…Reduced CD36 expression has been observed in the muscles of muscular dystrophy patients (Forst et al, 1998). SCD1 and SCD2 are integral membrane proteins of the endoplasmic reticulum and are implicated in the defective regulation of energy metabolism present in dystrophic muscle (Stamatikos et al, 2013). The increased expression of PPARg following tadalafil treatment seems to be specific to muscle tissue; it was also observed in an in vitro analysis on cultured myogenic cells.…”
Section: Discussionmentioning
confidence: 89%